2005
DOI: 10.1038/sj.bjc.6602499
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of HER-2/neu expression and gene amplification in patients with oesophageal squamous cell carcinoma

Abstract: The utilisation of antitumour T cells induced by cancer vaccination with HER-2 peptides or antibodies (Herceptin) against HER-2, as immunotherapy for oesophageal cancer, is a novel and attractive approach. It is important to clarify the frequencies of HER-2 expression and gene amplification in patients with oesophageal squamous cell carcinoma (SCC) and to evaluate the relationship between HER-2 status and HLA haplotype, since the candidates for HER-2 peptide-based vaccination are restricted to a certain HLA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 34 publications
(47 reference statements)
9
88
1
Order By: Relevance
“…With regard to the expression of HER-2 and EGFR on oesophageal SCC, EGFR-positive tumours were observed in 35% of patients with oesophageal SCC, and HER-2-positive tumours were observed in 31% of them in the present study, in line with previous reports (Mimura et al, 2005b). This result was the high-end of the data in literature showing HER-2 expression in oesophageal SCC varying between 0 and 31% (Sunpaweravong et al, 2005), in which the different rate of HER-2 expression seems to be due to the different criteria for evaluating the results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to the expression of HER-2 and EGFR on oesophageal SCC, EGFR-positive tumours were observed in 35% of patients with oesophageal SCC, and HER-2-positive tumours were observed in 31% of them in the present study, in line with previous reports (Mimura et al, 2005b). This result was the high-end of the data in literature showing HER-2 expression in oesophageal SCC varying between 0 and 31% (Sunpaweravong et al, 2005), in which the different rate of HER-2 expression seems to be due to the different criteria for evaluating the results.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, we and others have recently reported that the overexpression of EGFR of oesophageal SCC, partially accounted for by gene amplification, is found in 50 -70% (Itakura et al, 1994;Hanawa et al, 2006), and is indicative of a poor prognosis (Ozawa et al, 1989;Yano et al, 1991). Moreover, we showed that the overexpression of HER-2 in oesophageal SCC was found in 30.3% (Mimura et al, 2005b). These results indicated that oesophageal SCC shows a relatively high incidence of EGFR and/or HER-2 overexpression.…”
supporting
confidence: 74%
“…In particular, we and others have reported that the overexpression of EGFR is present in 50 -70% of oesophageal squamous cell carcinoma (ESCC) cases, and is indicative of a poor prognosis (Itakura et al, 1994;Hanawa et al, 2006). Moreover, we showed the overexpression of HER2 in 30% of ESCC cases (Mimura et al, 2005a). These results indicate that ESCC cases show a relatively high incidence of EGFR and/or HER2 overexpression, and that the HER family would be an attractive target for the treatment of ESCC.…”
supporting
confidence: 50%
“…These include increased sensitivity to certain cytotoxic chemotherapeutic agents, resistance to certain hormonal agents and increased propensity to metastasize to the brain (Ross et al, 2003;Gabos et al, 2006). HER2 overexpression and amplification is also seen in subsets of gastric, esophageal and endometrial cancers, also associated with worse disease (Mimura et al, 2005;Morrison et al, 2006;Yano et al, 2006) and also seen rarely in cancers of the oropharynx, lung and bladder (Hirsch et al, 2002;Khan et al, 2002;Latif et al, 2003). The etiologic role of HER2 overexpression in diseases other than breast cancer remain to be defined.…”
Section: Her2 Overexpression In Human Cancermentioning
confidence: 99%